Evaluation of Teacher Performance Using the WhatsApp Application in Online Learning - Khalilah Ramadhani; Diana Fachrurazi; Intan Maulina; Abdul Malik Karim Amrullah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Education during the Covid-19 pandemic has been carried out online, one of which is by using the WhatsApp application. For the sake of smooth learning, the principal as a supervisor must of course always evaluate the teacher as the main user of the WhatsApp Group so that educational goals can be achieved. This study aims to present evaluation procedures and aspects of teacher performance assessment at SDN 002 Rambah, Riau, Indonesia through the WhatsApp application. This study uses a qualitative approach with library and field research methods. Data were collected through observation, interviews, and documentation via cell phones. It started with observing learning activities in the WhatsApp Group, continued with communication via WhatsApp Call with the principal and four homeroom teachers. Then the data were analyzed based on the theory of Miles and Huberman by reducing the data, presenting the data, and concluding the field findings. The data obtained were validated by data triangulation techniques and data sources. The results showed that the evaluation procedure carried out by the principal was by joining the class WhatsApp group and conducting formative and summative evaluations online to teachers. So that aspects of teacher performance assessment, namely punctuality, initiative, ability, communication, and quality of work have shown satisfactory results marked by the smooth teaching and learning process, the ability of teachers to use technology, increased teacher professionalism, and good student achievement. The researcher recommends further research to see other alternatives that are used in teacher supervision and performance appraisal.